PERUBAHAN STATUS PERGURUAN TINGGI ISLAM (Studi Kasus IAIN Tulungagung) - Sulistyorini Sulistyorini (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2015)
The abilities of an institution, including an university, to accept, respond and adapt to a change becomes an important aspect to be survive. By having those abilities, it can be seen that some university cannot only be survive but also greatly develop, forexample IAIN Tulungagung. However, some universities still cannot show their progress. In other words, the change of their status does not lead them to significantly develop. The study is intended to explore deeply about the organization status change of an Islamic university ( A Case Study at IAIN Tulungagung). The focus of the study refers to the following two aspects, they are (a) how is the process of organization change at IAIN Tulungagung?, and (b) how is the model of management employed at IAIN Tulungagung after its organization change? Keywords: Organization Status Change, Islamic University, IAIN Tulungagung